THE MYSTERY OF DEATH IN THE POEM “PARIKSIT” BY GOENAWAN MOHAMAD - Baban Banita; Lina Meilinawati; Ari J. Purwawijana (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
Death is both a certainty and a mystery that is feared by most humans. As certainty, death raises the awareness that every living thing will definitely experience it. As a mystery, death seems on the verge of being obscure and full of secrets. The mystery here relates to the secrets of time, place, and causes of death. Certainty and mystery become an interesting combination of death. This allows the emergence of various behaviors in response to it. Therefore, there are always measures to avoid death or to keep lifelong. Death of unknown origin, he was present very secretly and full of surprise; death becomes a scary thing. Therefore, when a certainty arises that death will come and be due to a certain cause, the person concerned with all efforts will avoid that cause of death. This is illustrated in the poem “Pariksit” by Goenawan Mohamad. Pariksit is described as being cursed and about to die by the Dragon Taksaka. As a powerful king, he immediately put forth his efforts to prevent the Dragon from coming to him. This poetry will be analyzed using Rifaterre’s semiotic theory, which is an analysis with two stages of reading, namely heuristic reading which prioritizes the linguistic system and hermeneutic reading which emphasizes the analysis by looking for the hypnogram.